2013
DOI: 10.1158/1940-6207.capr-13-0081
|View full text |Cite
|
Sign up to set email alerts
|

Examining the Association between Oral Health and Oral HPV Infection

Abstract: Oral human papillomavirus (HPV) infection is the cause of 40% to 80% of oropharyngeal cancers; yet, no published study has examined the role of oral health in oral HPV infection, either independently or in conjunction with other risk factors. This study examined the relation between oral health and oral HPV infection and the interactive effects of oral health, smoking, and oral sex on oral HPV infection. Our analyses comprised 3,439 participants ages 30 to 69 years for whom data on oral HPV and oral health wer… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
67
4
1

Year Published

2013
2013
2022
2022

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 64 publications
(75 citation statements)
references
References 16 publications
3
67
4
1
Order By: Relevance
“…Few studies have examined this association, except one recently published study conducted in the United States (14). Using data from a nationally representative sample, the study demonstrated that self-reported poor oral health was an independent predictor of oral a mucosal HPV infection.…”
Section: Discussionmentioning
confidence: 98%
See 1 more Smart Citation
“…Few studies have examined this association, except one recently published study conducted in the United States (14). Using data from a nationally representative sample, the study demonstrated that self-reported poor oral health was an independent predictor of oral a mucosal HPV infection.…”
Section: Discussionmentioning
confidence: 98%
“…Only a few large studies have been conducted, mainly in the United Sates. The reported prevalence of oral HPV infection in these studies has ranged from approximately 2% to 8%, and HPV 16 is the type most commonly identified (11)(12)(13)(14)(15). Relevant risk factors have included male gender, oral sex, higher numbers of lifetime sexual partners, tobacco use, poor oral health, and cervical HPV infection (11)(12)(13)(14)(15).…”
Section: Introductionmentioning
confidence: 99%
“…[23][24][25][26][27][28] Notably, the prevalence of HPV seems to be significantly higher in men than in women. [25][26][27]29 Furthermore, high-risk sexual behavior including oral-genital sex has been found to be associated with transmission of HPV infections between oral and genital sites. 26,30,31 Immunodeficiency (e.g.…”
Section: Hpv Infection Of the Oral Cavitymentioning
confidence: 99%
“…A specific role was hypothesized way back in 1983, but till date, a definite consensus still awaits the light of the day [6][7][8]. The healthy adult population has showed prevalence for any HPV type of 2-8 % in OCSCC [9][10][11][12][13][14] with a higher preponderance for male sex worldwide [11][12][13]15] whereas previous Indian studies have reported a wide variation in HPV positivity prevalence from northeastern, eastern, and southern different regions of the country [16][17][18][19][20]. Further high-risk sexual behavior including oral genital sex and multiple sexual partners has been found to be associated with HPV transmission [12,21,22].…”
Section: Introductionmentioning
confidence: 99%